Public-Private Partnerships in Health : World Bank Group Engagement in Health PPPs - Independent Evaluation Group (World Bank, Washington, DC, 2016)
Access to essential health services is an important aspect of development. Governments from both developed and developing countries are increasingly looking at public-private partnerships (PPPs) as a way to expand access to higher-quality health services by leveraging capital, managerial capacity, and knowhow from the private sector. Originally confined to the traditional infrastructure sectors of transport, water, or energy, PPPs are increasingly applied also in social infrastructure sectors, particularly for delivery of health services. PPPs and other forms of private sector involvement in health are now also an important element of the World Bank Group’s response to country health challenges, as reflected in the 2013 World Bank Group Strategy, the 2008 World Bank Group Health Development Strategy, the 2015 joint World Bank Group Approach to Harnessing the Private Sector in Health, various CASs and CPFs and IFC’s FY17-19 and prior Strategy and Business Outlook reports. The objective of this review is to provide insights into the Bank Group’s work of applying PPP arrangements in the health sector, to distill knowledge with regard to what works (and what does not), review the quality of work in structuring PPP arrangements, and identify lessons to be learned from successful and failed efforts to structure health PPPs approved during FY04-15. The review encompasses all institutions of the Bank Group engaged in PPPs in health.